2007
DOI: 10.1021/ac070544k
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Analysis of Living Embryonic Stem Cells by Coherent Anti-Stokes Raman Microscopy

Abstract: Embryonic stem cells (ESC), derived from preimplantation embryos, are defined by their ability to both self-renew and differentiate into all of the cells and tissues of a mature animal. Efforts to develop methods for in vitro culture of ESC for research or eventual therapeutic applications are hampered by the lack of rapid, nondestructive assays for distinguishing ESC from other (differentiated) cells within a growing culture. Coherent anti-Stokes Raman scattering (CARS) microscopy is shown here to be a sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 22 publications
2
61
0
Order By: Relevance
“…In addition, the eventual use of this technology in future clinical cell-based transplantations for purifying and enriching cell populations would obviously require similar cell sorting instrumentation. It is anticipated that optical tweezers [42][43][44] for cell manipulation and advanced nonlinear Raman techniques such as CARS [45,46] and stimulated Raman scattering (SRS) to enhance the weak Raman scattering signals will be important components in future Raman-based cell sorting systems. A study using CARS for stem cell characterization has been reported [46], the results of which were in agreement with the Raman studies discussed above.…”
Section: Discussion and Future Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the eventual use of this technology in future clinical cell-based transplantations for purifying and enriching cell populations would obviously require similar cell sorting instrumentation. It is anticipated that optical tweezers [42][43][44] for cell manipulation and advanced nonlinear Raman techniques such as CARS [45,46] and stimulated Raman scattering (SRS) to enhance the weak Raman scattering signals will be important components in future Raman-based cell sorting systems. A study using CARS for stem cell characterization has been reported [46], the results of which were in agreement with the Raman studies discussed above.…”
Section: Discussion and Future Outlookmentioning
confidence: 99%
“…It is anticipated that optical tweezers [42][43][44] for cell manipulation and advanced nonlinear Raman techniques such as CARS [45,46] and stimulated Raman scattering (SRS) to enhance the weak Raman scattering signals will be important components in future Raman-based cell sorting systems. A study using CARS for stem cell characterization has been reported [46], the results of which were in agreement with the Raman studies discussed above. Recent studies have shown the proofof-principle concept of a novel Raman flow cytometer based on a laser tweezers Raman approach [47] and a coherent anti-Stokes Raman scattering (CARS) scheme [48] in combination with microfluidics to improve the speed and efficiency of analyzing the cells.…”
Section: Discussion and Future Outlookmentioning
confidence: 99%
“…Cells are selected under a microscope for data acquisition. This mode of data acquisition lends itself to the analysis of large numbers of cells, and has been used widely [40][41][42]51]. However, in the context of this chapter, another imaging based method for Ra-SCP data acquisition will be introduced.…”
Section: Sample Preparationmentioning
confidence: 99%
“…This method is more labor intensive, but yields in relatively short time hundreds of spectra of selected cellular features that show enormous sensitivity toward many biochemical processes, such as the metabolic activity in live yeast cells [38,39]. For example, this approach has been used very successfully to follow stem cell differentiation [40][41][42], photochemical changes in melanosomes [43] or for the detection of circulating tumor cells in flow cytometry [16,17]. Finally, due to the very high spatial resolution of Ra-SCP, spectral information from individual bacterial cells can be collected [44,45].…”
Section: Introductionmentioning
confidence: 99%
“…Konorov et al [10] also capitalized on the reflected F-CARS signal by placing their samples on mirrored cover slips to overlap the forward and backward scattered signals. Both groups attributed an enhancement of the detected signal in the epi-direction to the additional contributions from back-reflected F-CARS photons.…”
Section: Introductionmentioning
confidence: 99%